E-Learning during Lockdown of Covid-19 Pandemic: A Global Perspective - R.Radha, K.Mahalakshmi, Dr.V.Sathish Kumar, Dr.AR.Saravanakumar (International Journal of Control and Automation, 2020)
E-learning has become the mandatory component of all educational institutions like schools, colleges, and universities in and around the world due to the pandemic crisis of COVID-19. This deadly situation has flipped out the offline teaching process. E-learning provides an effective teaching method that brings out the best in students. To find out the student’s attitude towards e-learning, primary data has been collected from national and international wise through Google forms which include the student community from various schools, colleges, and universities. This research paper aims to study the E-learning process among students who are familiar with web-based technology. It also helps to find out solutions to improve the self-study skills of students. The stratified sampling method has been adopted in this study and the sample size is 175 across the world. The findings of the study reflect the impact of E-learning, students’ interest in using E-learning resources, and their performance. In conclusion, this study shows that E-learning has become quite popular among the students all over the world particularly, the lockdown period due to the COVID-19 pandemic.